Sistem Informasi Manajemen Surat Menggunakan Qr-Code Di Lingkungan Staff Personel Kodam V/Brawijaya - Riawan, Sembodo Tri Eko Nova; Muchayan, Achmad (Jusikom : Jurnal Sistem Komputer Musirawas, 2024)
Kodam is an extension of Regional Military Command. which has a position order under Mabesad (Army Headquarters). Kodam V / Brawijaya is a military command located in the East Java region and has an organizational structure starting from head level to staff level, one of which is Personnel Staff. Currently the correspondence system running at the Personnel Staff still uses a manual correspondence system. Filing incoming and outgoing letters still uses the hardcopy method which is made by officers which is very difficult. On this basis, in research it is necessary to create an information system regarding correspondence in the Personnel staff section of Kodam V/Brawijaya. Using a web-based mail management information system will simplify the process of searching archives for incoming and outgoing letters accurately, quickly and efficiently. The resulting system can document incoming and outgoing mail to make it easier to access when needed